Changes in gray matter volume after microsurgical lumbar discectomy: a longitudinal analysis - Luchtmann, Michael; Baecke, Sebastian; Steinecke, Yvonne; Bernarding, Johannes; Tempelmann, Claus; Ragert, Patrick; Firsching, Raimund (Frontiers in Human Neuroscience, 2015)
People around the world suffer chronic lower back pain. Because spine imaging often does not explain the degree of perceived pain reported by patients, the role of the processing of nociceptor signals in the brain as the basis of pain perception is gaining increased attention. Modern neuroimaging techniques (including functional and morphometric methods) have produced results that suggest which brain areas may play a crucial role in the perception of acute and chronic pain. In this study, we examined twelve patients with chronic low back pain and sciatica, both resulting from lumbar disc herniation. Structural magnetic resonance imaging (MRI) of the brain was performed one day prior to and about four weeks after microsurgical lumbar discectomy. The subsequent MRI revealed an increase in gray matter volume in the basal ganglia but a decrease in volume in the hippocampus, which suggests the complexity of the network that involves movement, pain processing, and aspects of memory. Interestingly, volume changes in the hippocampus were significantly correlated to preoperative pain intensity but not to the duration of chronic pain. Mapping structural changes of the brain that result from lumbar disc herniation has the potential to enhance our understanding of the neuropathology of chronic low back pain and sciatica and therefore may help to optimize the decisions we make about conservative and surgical treatments in the future. The possibility of illuminating more of the details of central pain processing in lumbar disc herniation, as well as the accompanying personal and economic impact of pain relief worldwide, calls for future large-scale clinical studies.